Bongso River Water Quality Status Due to Traditional Oil Mining Activities Using the Pollution Index Method - Ahmad Niamul Abrori; Laily Agustina Rahmawati; Heri Mulyanti (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Traditional petroleum mining activities in 137 old wells in Wonocolo Village, Bojonegoro Regency Council District, East Java, have a positive impact on the local community's economy, but also have a negative impact on the environment in the form of pollution of surface water. The study aims to determine the quality of the Bongso River in the traditional Wonocolo petroleum mining area based on physical and chemical parameters (temperature, pH, DO, TSS, TDS, COD, phenol, and nitrate), as well as analyze the level of pollution in the river using the Pollution Index method. The results of the Bongso River water quality analysis contained parameters that exceeded quality standards, namely, SB 1 station with COD levels of 47.1 mg / L and Phenol 0.196 mg / L. SB 2 station with TDS levels of 1010 mg / L, TSS 93.60 mg / L, COD 94.0 mg / L and phenol 0.552 mg / L. SB 3 station TDS levels 1190 mg / L, TSS 1778 mg/L, COD 84.7 mg/L, and phenol 0.747. Station SB 4 levels TDS worth 1450 mg / L, TSS 1019 mg / L, COD 28.2 mg / L, phenol 0.632 mg / L and DO levels do not meet the minimum quality standards of 3.4 mg / L. Station SB 5 levels TDS 1310 mg / L, COD 103.5 mg / L and phenol 0.364 mg / L. Station SB 6 levels TDS 1400 mg / L, COD 65.9 mg/L and phenol 0.585 mg/L. Station SB 7 levels TDS 1230 mg/L, TSS 54.80 mg/L and phenol 0.556 mg/L. Salinity of the Bongso River increased from upstream (SB1) to middle (SB2); 0 ppt to 4 ppt (rainy season). Water quality status using the IP method shows that SB 1 and SB 5 stations are categorized as Lightly Polluted. Meanwhile, SB 2, SB 3, SB 4, SB 6, and SB 7 stations are categorized as Moderately Polluted.